Participatory variety selection in wheat and its impact on scaling-up seed dissemination and varietal diversity (Bangladesh Journal of Agricultural Research, 2008)
Participatory selection was conducted at the Wheat Research Centre, Bangladesh Agricultural Research Institute (BARI), Dinajpur to facilitate farmers in selecting and disseminating their preferable variety and replace widely cultivated disease susceptible Kanchan to increase wheat yield and production. Farmers need for wheat variety was identified through participatory rural appraisal in 2002 and impacts were assessed by house hold level survey in 2005. Researches were conducted as mother and baby trials. Scaling-up seed dissemination was carried out through seed supply. BAW1008, Shatabdi, and BAW 1006 produced higher yield in both mother and baby trials and got higher scores for farmers overall preference. The farmers emphasized on yield together with bold and white grains, more grains/spike, strong stem and other characters during scoring. They identified BAW 966, BAW 1006, BAW 1008, and Shatabdi for good Chapati quality. They expected to cultivate BAW1008, Shatabdi, and BAW 1006 in the following years. Farmer to farmer seed dissemination was highly satisfactory and seeds of Shatabdi reached 47% wheat farmers of the villages in 2004-05. Varietal diversity was increased remarkably and seven varieties were grown in the study villages. The area of Kanchan came down from 100% (in 2002-03) to 24% (in 2005-06). The participating personnel were hopeful to the new concept of plant breeding and expecting its widespread use in the country. DOI: http://dx.doi.org/10.3329/bjar.v32i3.549Bangladesh J. Agril. Res. 32(3) : 473-486, September 20